2017
DOI: 10.7554/elife.28975
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear microenvironments modulate transcription from low-affinity enhancers

Abstract: Transcription factors bind low-affinity DNA sequences for only short durations. It is not clear how brief, low-affinity interactions can drive efficient transcription. Here, we report that the transcription factor Ultrabithorax (Ubx) utilizes low-affinity binding sites in the Drosophila melanogaster shavenbaby (svb) locus and related enhancers in nuclear microenvironments of high Ubx concentrations. Related enhancers colocalize to the same microenvironments independently of their chromosomal location, suggesti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
139
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(154 citation statements)
references
References 60 publications
15
139
0
Order By: Relevance
“…In agreement with this model, several TFs (Bicoid [Mir et al, 2017[Mir et al, , 2018, Dorsal [Yamada et al, 2019], Zelda [Dufourt et al, 2018;Mir et al, 2018] and Ultrabithorax [Tsai, Alves, & Crocker, 2019;Tsai et al, 2017]) are present in foci or "hubs" in the nucleus. interact with nascent sites of transcription, suggesting a "hit and run" mechanism for initiating transcription (Mir et al, 2018), rather than a model where TFs become integrated with stable PolII/Med clusters.…”
Section: Bridging the Timescale And Concentration Gap: Hubs?supporting
confidence: 71%
See 1 more Smart Citation
“…In agreement with this model, several TFs (Bicoid [Mir et al, 2017[Mir et al, , 2018, Dorsal [Yamada et al, 2019], Zelda [Dufourt et al, 2018;Mir et al, 2018] and Ultrabithorax [Tsai, Alves, & Crocker, 2019;Tsai et al, 2017]) are present in foci or "hubs" in the nucleus. interact with nascent sites of transcription, suggesting a "hit and run" mechanism for initiating transcription (Mir et al, 2018), rather than a model where TFs become integrated with stable PolII/Med clusters.…”
Section: Bridging the Timescale And Concentration Gap: Hubs?supporting
confidence: 71%
“…This "bursty" transcription has been formalized as a two state model of a promoter's activity, which cycles between ON and OFF states with stochastic rate constants (Larson, Singer, & Zenklusen, 2009;Peccoud & Ycart, 1995 The formation of PolII clusters or aggregates is thought to be driven by weak interactions between intrinsically disordered regions/low complexity domains (LCD) in PolII and other proteins (Boehning et al, 2018;Cho et al, 2018;Lu et al, 2018). Similarly, many TFs In agreement with this model, several TFs (Bicoid [Mir et al, 2017[Mir et al, , 2018, Dorsal [Yamada et al, 2019], Zelda [Dufourt et al, 2018;Mir et al, 2018] and Ultrabithorax [Tsai, Alves, & Crocker, 2019;Tsai et al, 2017]) are present in foci or "hubs" in the nucleus. Similarly, many TFs In agreement with this model, several TFs (Bicoid [Mir et al, 2017[Mir et al, , 2018, Dorsal [Yamada et al, 2019], Zelda [Dufourt et al, 2018;Mir et al, 2018] and Ultrabithorax [Tsai, Alves, & Crocker, 2019;Tsai et al, 2017]) are present in foci or "hubs" in the nucleus.…”
Section: Dynamics Of Dna Binding and Transcriptionmentioning
confidence: 98%
“…Recent studies have suggested that phase-separated condensates of molecules involved in transcription form at enhancers (Boija et al, 2018;Cho et al, 2018;Chong et al, 2018;Fukaya et al, 2016;Hnisz et al, 2017;Sabari et al, 2018;Tsai et al, 2017), providing a potential mechanism for concentrating transcriptional machinery at specific loci. Here we investigated how features encoded in a DNA element regulate the formation of transcriptional condensates.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggest that the cooperative process of phase separation can also contribute to assembling dynamic clusters or condensates of TFs, coactivators, and RNA polymerase II at active enhancer elements, especially super-enhancers (Boija et al, 2018;Cho et al, 2018;Chong et al, 2018;Fukaya et al, 2016;Hnisz et al, 2017;Sabari et al, 2018;Tsai et al, 2017). Some of these transcriptional condensates contain hundreds of coactivator and RNA polymerase II molecules (Cho et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In the first model, increasing the concentration of NICD when the enhancer is activated would create larger PolII clusters. This is based on the observation that low complexity activation domains in transcription factors can form local regions of high concentration of transcription factors, so-called "hubs", which in turn are able to recruit PolII (Mir et al 2017;Tsai et al 2017;Lu et al 2018). As the lifetime of PolII clusters appears to correlate with transcriptional output (Cho et al 2016), the formation of larger PolII clusters would in turn drive larger bursts.…”
Section: Nicd Regulates Transcription Burst Sizementioning
confidence: 99%